Investigating the exponential age distribution of firms - Alex Coad (Max Planck Institute of Economics, 2009)
While several plots of the aggregate age distribution suggest that firm age is exponentially distributed, we find some departures from the exponential benchmark. At the lower tail, we find that very young establishments are more numerous than expected, but they face high exit hazards. At the upper tail, the oldest firms are older than the exponential would have predicted. Furthermore, the age distribution of international airline companies displays multimodality. Although we focused on departures from the exponential, we found that the exponential was a useful reference point and endorse it as an appropriate benchmark for future work on industrial structure.
Keywords: L20; L25; L11; 330; Age distribution; Exponential distribution; Firm size distribution; Survival